Do ecologically close species shift their daily activities when in sympatry? A test on chamois in the presence of mouflon. (23rd January 2014) - Darmon, Gaëlle; Bourgoin, Gilles; Marchand, Pascal; Garel, Mathieu; Dubray, Dominique; Jullien, Jean‐Michel; Loison, Anne
<x xml:space="preserve">Abstract</x> Temporal partitioning of daily activities between species may promote coexistence within animal communities by reducing behavioural interference, particularly when species highly overlap in the use of space and resources. Such a strategy may be used by Alpine chamois (Rupicapra rupicapra rupicapra) when in the presence of mouflon (Ovis gmelini musimon × Ovis sp.), an introduced highly gregarious species with a broader ecological niche, overlapping with that of chamois. Using simultaneous monitoring of 29 Global Positioning System‐collared chamois and 12 mouflon, we assessed the temporal variation in activity patterns of chamois amongst two subpopulations: one without mouflon and one with mouflon, during January and August, which are the two most extreme periods of spatial overlap of mouflon with chamois distribution. Substantial differences in activity patterns between chamois and mouflon were observed (mean 13.8 ± 10.5% in January and 10.6 ± 11.6% in August). More subtle differences appeared between both subpopulations of chamois and persisted, regardless of the spatial overlap with mouflon (3.2 ± 1.8% in January and 2.6 ± 1.5% in August), thus highlighting that there is no behavioural interference from mouflon on chamois. Our findings suggest that the temporal partitioning of daily activities between chamois and mouflon, although probably a result of species‐specific adaptations to environmental conditions, may contribute to their coexistence. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 621–626.